In Vitro and In Vivo Characterization Methods for Evaluation of Modern Wound Dressings - Naveed Ahmad (Pharmaceutics, 2022)
Chronic wound management represents a major challenge in the healthcare sector owing to its delayed wound-healing process progression and huge financial burden. In this regard, wound dressings provide an appropriate platform for facilitating wound healing for several decades. However, adherent traditional wound dressings do not provide effective wound healing for highly exudating chronic wounds and need the development of newer and innovative wound dressings to facilitate accelerated wound healing. In addition, these dressings need frequent changing, resulting in more pain and discomfort. In order to overcome these issues, a wide range of affordable and innovative modern wound dressings have been developed and explored recently to accelerate and improve the wound healing process. However, a comprehensive understanding of various in vitro and in vivo characterization methods being utilized for the evaluation of different modern wound dressings is lacking. In this context, an overview of modern dressings and their complete in vitro and in vivo characterization methods for wound healing assessment is provided in this review. Herein, various emerging modern wound dressings with advantages and challenges have also been reviewed. Furthermore, different in vitro wound healing assays and in vivo wound models being utilized for the evaluation of wound healing progression and wound healing rate using wound dressings are discussed in detail. Finally, a summary of modern wound dressings with challenges and the future outlook is highlighted.